USING DIGITAL DISCUSSION THROUGH COMMENTING BLOG TO IMPROVE STUDENTS’ ABILITY IN WRITING ANALYTICAL EXPOSITION TEXT (ELT Forum: Journal of English Language Teaching, 2013)
The aim of the study is to find out whether using video-typed nursery rhymes can enhance speaking ability of young learners of grade four of Elementary School. The subject of the study were 19 students of class four Al-Khawaritzmi of SD Islam Bilingual An-Nissa Semarang. The research applied was experimental research and the research design was one group pretest-posttest. In the research, the students were taught using video-typed nursery rhymes. The result of this research was found by comparing the result of pretest and posttest. The researcher used t-test to find out the significance enhancement. Based on the result of the study, there were some enhancement in students’ speaking ability after they were given the treatment using video-typed nursery rhymes. After getting the treatment, the students were able to absorb the lesson better by being taught using video-typed nursery rhymes than using the usual way of teaching. The colorful video and the cheerful melody of the nursery rhymes gave some fun and happy atmosphere inside the classroom. The students understood easily for they enjoyed the lesson. The conclusion taken from the study is that the video-typed nursery rhymes can enhance the students’ speaking ability and suitable for teaching speaking.